A valid, practical, and effective transformational leadership–based educational management model for improving elementary school teachers’ performance in padang lawas regency - Astri Novia Siregar (Lembaga Riset Mutiara Akbar, 2026)
This study aims to develop a transformational leadership–based educational management model that is valid, practical, and effective for improving elementary school teachers’ performance in Padang Lawas Regency, North Sumatra. The research was motivated by suboptimal teacher performance caused by conventional principal leadership practices and the limited integration of management functions with transformational leadership principles. The study employed a Research and Development (R&D) approach based on the Borg and Gall model, involving stages from preliminary study to final product refinement. Participants included principals and teachers from public elementary schools in Sosopan District. Data were collected through interviews, observations, questionnaires, documentation, and testing, and analyzed using qualitative and quantitative techniques, including validity, reliability, and effectiveness analysis. The results indicate that the developed model meets high criteria of validity, practicality, and effectiveness. Implementation across three trial stages demonstrated significant improvements in principals’ transformational leadership dimensions and teacher performance in planning, implementation, and evaluation of learning. The findings suggest that integrating educational management functions with transformational leadership principles can systematically enhance teacher performance and support sustainable school quality improvement.